PENGARUH DUKUNGAN MANAJEMEN PUNCAK DAN KEMAMPUAN TEKNIK OPERATOR SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS INFORMASI AKUNTANSI (Studi pada Lembaga Keuangan Mikro di Kota Banda Aceh) - Ikhsan, Muammar; Bustamam, Bustamam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This study aimed to examine the effect of top management support and the operator technical ability accounting information system on the quailty of information system at micro finnance institutions in Banda Aceh. The sampling method using census method. In this study the data needed all population sampled 51 people. The collection of data and information needed in the study conducted by the research field. The data used is primary data obtained directly from the subject of research in the form of a questionnaire. Assessment of the effect of independent variables on the dependent variable is done by using a multiple regression model using SPSS 20. The results showed that either partially or simultaneously, top management support and the operator technical ability affects the quailty of information system at micro finnance institutions in Banda Aceh. Keywords top management support, the operator technical ability, accounting information system, quality of information system and micro finnance institution.